A method for speech watermarking in speaker verification - Syed Mohamed, Syed Abdul Rahman Al-Haddad; Saripan, M. Iqbal; C. Doraisamy, Shyamala; Ramli, Abd Rahman; Nematollahi, Mohammad Ali (2013)
The present invention relates to a method for speech watermarking in speaker verification, comprising the steps of: embedding watermark data into speech signal at a transmitter; and extracting watermark data from the speech signal at a receiver; characterised by the steps of: selecting frames having least speaker-specific information from the speech signal to carry watermark data; detecting voice activity to detect presence or absence of speaker’s voice in the speech signal; and embedding watermark data into the selected frames of the speech signal according to the presence or absence of the speaker’s voice.